Mobile reporting of vaccine stock-levels in primary health care facilities in the Eastern Cape Province of South Africa: perceptions and experiences of health care workers - Chinwe Juliana Iwu; Ntombenhle Ngcobo; Sara Cooper; Lindi Mathebula; Hlokoma Mangqalaza; Abongile Magwaca; Usuf Chikte; Charles S. Wiysonge (Taylor & Francis Group, 2020)
The use of mobile and wireless digital technologies - mobile health (mhealth)- is increasingly been adopted in low- and middle-income countries (LMICs) to improve data visibility, improve decision-making, and consequently help ensure availability of health commodities in health facilities. In a bid to improve availability of medicines in primary health care facilities, the South African department of Health launched the Stock Visibility Solution (SVS), a mobile application developed for the purpose of capturing and monitoring stock levels of medicines including vaccines using mobile phones. The stock levels of medicines in facilities are usually uploaded to the central stock management system so that managers can act promptly to address stock-out situations. Pilot studies show that the SVS has the potential to reduce stock-outs from occurring. This study aimed to explore the perceptions and experiences of the SVS system amongst healthcare workers (HCWs) who are involved with managing stock levels of medicines in primary health care facilities in the Eastern Cape Province. This will help identify potential barriers and facilitators to implementation of the system and contribute to the development of strategies to improve its efficiency and effectiveness. A qualitative research design was employed, including semi-structured interviews with 64 HCWs working in primary health care facilities in the OR Tambo district, Eastern Cape Province in South Africa. Data was transcribed verbatim and analyzed using thematic analysis. Most HCWs understood the SVS as a system for reporting stock levels to managers and conveyed commitment to ensuring the system works. However, they highlighted a number of factors that demotivated efficient usage of the system: inadequate training, staff shortages and high staff turnover, lack of responses from the managers, the extra workload that comes with the system, amongst others. HCWs made various suggestions for how the system might be improved, most pertinently the need for more pharmacists and pharmacy assistants and for these cadres to be primarily in-charge of stock management and the use of the SVS. While HCWs are committed to addressing vaccine stock-outs, they face various barriers to an effective and efficient implementation of the SVS system. We make various recommendations for how these barriers might be addressed.